2012
DOI: 10.1111/j.1365-2265.2012.04386.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GH dose after the catch‐up growth period maintains metabolic outcome in short prepubertal children with and without classic GH deficiency

Abstract: Continued reduced individualized GH treatment after the catch-up growth period is safe and reduces hyperinsulinism. Individualized GH dose can be reduced once the desired height(SDS) is achieved to avoid overtreatment in terms of metabolic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Demonstration of the efficacy of lower mean GH doses (0.18 and 0.24 mg/kg/week) during the maintenance phase of the treatment of patients with ISS suggests that growth during the post-catch-up phase is not GH dose dependent and, therefore, represents an important finding that differs from the traditionally held belief that patients with ISS generally require higher-than-average GH dosing due to intrinsic GH resistance [5,16,18]. Our finding is in agreement with that of Decker et al [19], who studied 27 children with ISS who had their GH doses reduced by 50% after an initial 2-year catch-up phase. The authors found that ‘… serum IGF-I is no longer the major growth factor in the maintenance growth period when channel-parallel growth has been achieved.'…”
Section: Discussionsupporting
confidence: 71%
“…Demonstration of the efficacy of lower mean GH doses (0.18 and 0.24 mg/kg/week) during the maintenance phase of the treatment of patients with ISS suggests that growth during the post-catch-up phase is not GH dose dependent and, therefore, represents an important finding that differs from the traditionally held belief that patients with ISS generally require higher-than-average GH dosing due to intrinsic GH resistance [5,16,18]. Our finding is in agreement with that of Decker et al [19], who studied 27 children with ISS who had their GH doses reduced by 50% after an initial 2-year catch-up phase. The authors found that ‘… serum IGF-I is no longer the major growth factor in the maintenance growth period when channel-parallel growth has been achieved.'…”
Section: Discussionsupporting
confidence: 71%
“…Risk of bias was assessed using the Cochrane risk-of-bias tool based on the following criteria: random sequence generation, allocation concealment, the blinding of participants and personnel, the blinding of outcome assessment, the completeness of outcome data, the selectivity of reporting, and other bias [ 15 ]. Judgements were expressed as “low risk,” “high risk,” or “unclear risk.”…”
Section: Methodsmentioning
confidence: 99%